The siege - Lasky, Kathryn (New York : Scholastic, 2004)
"Enraged by his clash with Soren and driven by and all-consuming desire for power, Kludd and his group, the Pure Ones, launch an attack upon the Great Ga'Hoole Tree. The noble owls who live there must fight fiercely to protect their resources and defend their honor"--Page 4 of cover.
1. Pilgrim -- 2. Watcher in the Woods -- 3. At the Great Ga'Hoole Tree -- 4. Sprink on Your Spronk! -- 5. Mission Most Dreadful -- 6. Learning by Heart and by Gizzard -- 7. Special Flint Mop -- 8. Across the Sea and to the St. Aegolius Canyons -- 9. Most Dreadful Place on Earth -- 10. To Fear the Moon -- 11. Flecks in the Nest -- 12. World According to Otulissa -- 13. Rogue Smith Is Called -- 14. Escape -- 15. Old Friend Discovered -- 16. Let Us Fly, Mates! Let Us Fly! -- 17. Sodden Book -- 18. Great Tree Prepares -- 19. At War -- 20. News Is Not Good -- 21. Besieged -- 22. Coo-Coo-Coo-Roo -- 23. Last Battle -- 24. New Constellation Rises.
Keywords: Owls -- Juvenile fiction; Fantasy fiction